Geometrical Effects of Duct on the Entropy Generation in the Laminar Forced Convection Separated Flow - Nasrin Aminzadeh; Shima Sotoodehnia; Meysam Atashafrooz (International Journal of Advanced Design and Manufacturing Technology, 2018)
In this research paper, irreversibility analysis of laminar forced convection flow in a duct with variable cross-section are numerically studied. Two-dimensional Cartesian coordinate system is used to solve the set of governing equations and also the blocked-off method is considered for simulation of the inclined surfaces. To obtain the velocity and temperature fields, the basic equations are numerically solved using the finite volume method and SIMPLE algorithm. To determine the flow irreversibility, the entropy generation number is calculated according to the thermodynamic second law. The geometrical effects of duct on the distributions of streamlines, friction coefficient, Nusselt number, entropy generation, and Bejan number are presented with details. The results show that the duct heights and inclination angle of surfaces have great effects on the flow irreversibility and the hydrodynamics and thermal behaviours. Also, comparison of the present numerical results with the available data published in the open literature shows an excellent consistency.